Sv. Dujam i sv. Anastazije u hagiotopografiji Hrvatske - Badurina, Anđelko; Galović, Tomislav (2014)
Na temelju baze podataka Hagiotopografija Hrvatske, drugih istraživanja i dosadašnje literature, u radu je donesen popis do danas poznatih svetih mjesta u Hrvatskoj posvećenih sv. Dujmu i sv. Anastaziju, dok će se u dva navrata radi potpunosti obraditi i područje koje prelazi ove granice. Na taj se način ukazuje na raširenost štovanja sv. Dujma i sv. Anastazija duž istočne jadranske obale – od Istre na sjeveru do Dubrovnika i Kotora na jugu – točnije na današnjim jurisdikcijskim područjima Splitsko-makarske, Riječke i Zadarske nadbiskupije, odnosno Porečke i Pulske, Krčke, Gospićko-senjske, Hvarskobračko- viške, Dubrovačke i Kotorske biskupije. U nekoliko primjera zabilježeno je kolik je bio njihov utjecaj na prostoru i u životu ljudi. Rad je popraćen dvama kartografskim prilozima (geografska rasprostranjenost) i jednim grafikonom (približna datacija sakralnih građevina koje se obrađuju), kao i nekim statističkim podatcima vezanim za svetomjestopis Hrvatske u cjelini.
This paper, drawing on the database Hagiotopography of Croatia gives a list of all the known holy sites in Croatia dedicated to SS. Domnius and Anastasius while twice for the sake of completeness it covers what exceeds these borders. The database provides the ability to search according to a number of criteria: according to the saint ; the adjective of the saint ; the area in which the consecrated site is located ; the bishopric of the site ; the parish of the holy site ; the style of building and the number of naves (aisles) ; the number of apses ; the types of apse ; the feast day of the saint ; time of building of the consecrated place ; the coverage of the protection of the saint ; the locality of the holy place and the attribute of the saint. Accordingly, an indication of the wide diffusion of the veneration of St Domnius and St Anastasius along the eastern Adriatic coast is given – from Istria in the north to Dubrovnik and Kotor in the south, that is, in the jurisdictions of the archdioceses of Split and Makarska, Rijeka and Zadar, the dioceses of Poreč and Pula, Krk, Gospić and Senj, Hvar, Brač and Vis, Dubrovnik and Kotor. The research carried out revealed a total of 21 places within the Croatian hagiotopography dedicated to St Domnius and 14 to St Anastasius. Of these, some of the churches are completely preserved, some exist in the form of archaeological remains, while some are only registered in written sources or folk tradition. A few have had their dedicatee changed in the course of time. Several examples are recorded of the great extent of their influence on the space and people’s lives. According to chronological and stylistic-architectural analysis we can only give approximate data (what is called relative chronology: the first recorded data, artistic, stylistic and architectural features). Most of the churches dedicated to St Domnius and St Anastasius date from the Middle Ages or the early modern period (a somewhat more pronounced jump favouring St Anastasius being seen in the 20th century). The greatest concentration of churches, as well as of veneration of St Domnius and St Anastasius, is precisely in the area where both of them underwent their deaths as martyrs, and it is in this area that they have been the object of lasting veneration among the common people. The paper has two maps (of distribution) and a graph (approximate dating of the religious buildings considered), as well as certain statistical data related to the list of holy places of Croatia as a whole.
Projekt MZOS
Projekt MZOS
HRV